Perbandingan Kinerja dengan Balance Scorecard Perspektif Keuangan pada Bank Syariah BUMN di Indonesia - Meilani, Reka (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
The aims of study were to know and analyze the performance of Bank Syariah BUMN in Indonesia seen in the concept of Balance Scorecard, especially financial perspective and compare financial performance. This study was a descriptive study that explains a picture of a particular object and result. This study described the performance appraisal results from the financial perspective of Bank Syariah Mandiri, BNI Syariah, BRI Syariah in 2016. The type of data used in this study were secondary data in the form of financial data of Bank Syariah Mandiri, BNI Syariah, BRI Syariah, which has been published year 2016. The data source is obtained from Indonesian Banking Directory published by Bank Indonesia, from the Indonesia Stock Exchange website. Methods of data analysis used descriptive analysis. Based on the performance analysis of Balancae Score Card with financial perspective, it can be concluded that BRI Syariah, BNI Syariah and Bank Mandiri Syariah has a good performance in 2016. Capital ratio, Earning Assets Quality (KAP) Ratio, Profitability Ratio (earnings), Liquidity Ratio (liquidity) and Sensitivity to market risk in BRI Syariah pertained good. Capital Ratio (Capital), Earning Asset Quality (KAP) Ratios, Profitability Ratio (earnings), Liquidity Ratio (liquidity) and Sensitivity to Market Risk (BNI Syariah) were good. Capital Ratio (Capital), Earning Asset Quality (KAP) Ratios, Profitability Ratios (earnings), Liquidity Ratio (liquidity) and Sensitivity to market risk in Bank Syariah Mandiri were good. Based on the comparison of capital ratio, earning asset ratio, liquidity ratio and sensitivity to market risk in Bank Syariah Mandiri, BNI Syariah and BRI Syariah, in general the largest ratio were the ratio of BRI Syariah except capital ratio, both BNI Syariah except liquidity ratio and except market sensitivity.